Evaluating an accessible web interface for older adults – the impact of mild cognitive impairment (MCI). Issue 4 (21st December 2015) - Haesner, Marten; Steinert, Anika; O'Sullivan, Julie Lorraine; Steinhagen-Thiessen, Elisabeth
Abstract : Purpose: – Cognitive changes occur with age and cognitive limitations can negatively influence computer use. Human-interaction studies show that especially older adults benefit considerably from using web platforms. The purpose of this paper is to measure the possible impact of cognitive impairment in web usability and to analyse the differences between older adults with and without cognitive impairment. Design/methodology/approach: – In the presented pilot study, 50 older adults tested a web-based interface on a PC and tablet computer that was designed based on a styleguide for this specific user group. In two sessions participants had to conduct six tasks. In a third session older adults were left unsupervised in the laboratory where they were confronted with unexpected events triggered by a principal investigator. Findings: – The performance results differed significantly between the two groups. Older adults with mild cognitive impairment (MCI) needed more time and were more likely to make mistakes when using a web platform. After analysing error data, it became apparent that errors made by older adults with MCI occurred due to a lack of orientation in websites. Originality/value: – Little is known about web performance of older adults with cognitive impairment. The authors present valid data of this interesting target group and reveal their specific problems when handling a new online platform. The importance of a flat website hierarchy can be essential in developing senior friendly web pages. The authors also highlight methodological issues and illustrate the importance of qualitative information of the usability data, e.g. the different types of problems or errors.